1977
DOI: 10.1246/cl.1977.563
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Strontium Ion From a Large Amount of Calcium Ion by the Use of a Macrocyclic Ether

Abstract: A small amount of Sr2+ (0.7∼20 mg) was simply separated from a large amount of Ca2+(1.5 g) by liquid–liquid extraction using dicyclohexyl-18-crown-6 chloroform solution. Average recovery of Sr2+ was 97 %, and the amount of Ca2+ in the final strontium fraction of the separation was decreased to 10−4∼10−5 part of the initial amount.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Major part of the earlier work in this direction involved extraction from alkaline or weakly acidic solutions employing large organophilic counter anions such as picrate [5,6], Blasius et al [7], have employed DCH18C6 in 1,1,2,2-tetrachloroethane for extraction of Sr from 2 M HNO3 without using any counter anion. It has been reported that the presence of tributyl phosphate (TBP) and didodecyl naphthalene sulphonic acid (DDNS) enhanced the extraction ability of the substituted crown Compounds in toluene and reasonable Sr extraction was achieved by Gerow et al [8], at 3 M HNO3.…”
Section: Introductionmentioning
confidence: 99%
“…Major part of the earlier work in this direction involved extraction from alkaline or weakly acidic solutions employing large organophilic counter anions such as picrate [5,6], Blasius et al [7], have employed DCH18C6 in 1,1,2,2-tetrachloroethane for extraction of Sr from 2 M HNO3 without using any counter anion. It has been reported that the presence of tributyl phosphate (TBP) and didodecyl naphthalene sulphonic acid (DDNS) enhanced the extraction ability of the substituted crown Compounds in toluene and reasonable Sr extraction was achieved by Gerow et al [8], at 3 M HNO3.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is well known that Sr 2+ reacts with 18-crown-6 derivatives to form cationic 1:1 complexes in ionpair extraction to organic solvents [2][3][4][5][6] and ion-exchange extraction to ILs. [7][8][9] Namely, in the Sr extraction with DC18C6 alone, it was expected that the extraction equilibrium is expressed as follows:…”
Section: Extracted Species and Equilibrium In The Single-extractant Smentioning
confidence: 99%
“…1 Several 18-crown-6 derivatives, neutral macrocyclic ligands with suitable cavity size (260 -320 pm for 18-crown-6) for complexation to Sr 2+ (ionic radius = 132 pm), have been used for extraction of Sr to polar or aromatic organic solvents as ion-pair with picrate or other counteranion since the 1970s [2][3][4] up to the present. 1,5,6 Moreover, several researchers have investigated the possible use of hydrophobic ionic liquids (ILs) as extraction solvents for Sr with the 18-crown-6 derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has focused on the development of a workable acid-side liquid-liquid extraction process for the removal of strontium. Kimura et al (1977), for example, utilized one of the macrocyclic polyethers (dicyclohexano-18-crown-6) to separate "Sr from milk. This crown ether was observed as ineffective in highly acid samples, a significant limitation.…”
Section: Novel Chromatographic Chemicalsmentioning
confidence: 99%